Counter-colonial criminology : a critique of imperialist reason - Agozino, Biko (London ; Sterling, VA : Pluto Press, 2003)
'A groundbreaking book ... [offering] dazzling brilliance in the development of criminological theory.' Ihekwoaba D. Onwudiwe, Associate Professor, University of Maryland Eastern Shore.
Includes bibliographical references (pages 248-265) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Criminology; Imperialism; Criminologie; Impérialisme.; criminology; SOCIAL SCIENCE -- Criminology; POLITICAL SCIENCE -- Human Rights; Criminology; Imperialism